Taking your iPod touch to the max - Grothaus, Michael; Sadun, Erica ([Berkeley, Calif.] Apress, 2011)
Unleash your iPod touch and take it to the limit using secret tips and techniques. Fast and fun to read, Taking Your iPod touch 5 to the Max will help you get the most out of iOS 5 on your iPod touch. You?ll find all the best undocumented tricks, as well as the most efficient and enjoyable introduction to the iPod touch available. Starting with the basics, you?ll quickly move on to discover the iPod touch's hidden potential, like how to connect to a TV and get contract-free VoIP. From e-mail and surfing the Web, to using iTunes, iBooks, games, photos, ripping DVDs and getting free VoIP with Skype or FaceTime?whether you have a new iPod touch, or an older iPod touch with iOS 5, you'll find it all in this book. You?ll even learn tips on where to get the best and cheapest iPod touch accessories. Get ready to take iPod touch to the max
Annotation Unleash your iPod touch and take it to the limit using secret tips and techniques. Fast and fun to read, Taking Your iPod touch 5to the Maxwill help you get the most out of iOS 5 on your iPod touch.Youll find all the best undocumented tricks, as well as the most efficient and enjoyable introduction to the iPod touch available. Starting with the basics, youll quickly move on to discover the iPod touch's hidden potential, like how to connect to a TV and get contract-free VoIP.From e-mail and surfing the Web, to using iTunes, iBooks, games, photos, ripping DVDs and getting free VoIP with Skype or FaceTimewhether you have a new iPod touch, or an older iPod touch with iOS 5, you'llfind it all in this book. Youll even learn tips on where to get the best and cheapest iPod touch accessories. Get ready to take iPod touch to the max!What youll learnHow to get your music, videos, and data onto your iPod touchHow to manage your mediaTips for shopping in the App Store and iTunes StoreGetting the most out of iBooksUsing Mail on your iPod touchKeeping in touch with FaceTimeWho this book is forAnyone who wants to get the most out of their iPod touch 5.Table of ContentsBringing Home the iPod touchPutting Your Data and Media on the iPod touchInteracting with Your iPod touchBrowsing with Wi-fi and SafariTouching Photos and VideosTouching Your MusicShopping at the iTunes StoreShopping at the App StoreReading and Buying Books with iBooksSetting Up and Using MailStaying on Time and Getting ThereUsing your Desk SetPhotographing and Recording the World Around YouVideo Calling with FaceTimeCustomizing Your iPod touch
"iOS 5 edition"--Cover.
Electronic reproduction.
Keywords: iPod (Digital music player) -- Handbooks, manuals, etc; Digital music players -- Handbooks, manuals, etc; Portable media players -- Handbooks, manuals, etc; Pocket computers -- Handbooks, manuals, etc